Answer:
![Tn\text{ = -}(4)/(3)(-3)^(n-1)](https://img.qammunity.org/2023/formulas/mathematics/college/wmvjsp5oazwetwkvtq7owf153otwsjo8wv.png)
Step-by-step explanation:
The nth term of a geometric sequence is expressed as;
![\text{T}_{n\text{ }}=ar^(n-1)](https://img.qammunity.org/2023/formulas/mathematics/college/hlgv1qhz821orkcv9hkaonpirf82iwk96n.png)
If the second term is 4;
![\begin{gathered} T_2=\text{ ar} \\ T_{2\text{ }}=\text{ ar= 4} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/2bv18ckwb6gqbujoft1aoqknc2leihvspc.png)
If the third term is -12, hence;
![\text{T}_{3\text{ }}=ar^2\text{= -12}](https://img.qammunity.org/2023/formulas/mathematics/college/ob2t4kbuod8s6re4zm00809mo8joddidvg.png)
Solve equation 1 and 2 simultaneously for a and r
Divide both expressions
![\begin{gathered} (ar)/(ar^2)=\text{ }(4)/(-12) \\ (1)/(r)=(4)/(-12) \\ r\text{ = -12/4} \\ r\text{ = -3} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/c14d1vbyp8wfbdv7dvqpffd8s7zzjv889a.png)
Get the first term;
Substitute r = -3 into 1;
Frm 1;
![\begin{gathered} ar\text{ = 4} \\ -3a\text{ = 4} \\ a\text{ = }(-4)/(3) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/1d1x8etw7k3vfer4f51p7vmqpc1dt8jyeb.png)
Get the explicit expression;
![\begin{gathered} Tn=ar^(n-1) \\ Tn\text{ =-}(4)/(3)(-3)^{n-1^{}^{}} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ca24sz1bjyrrycpcj9hzmd4f1ja6y2znnr.png)
This gives the required answer